Long non-coding RNA CCAT2 promotes cell proliferation and invasion through regulating Wnt/β-catenin signaling pathway in clear cell renal cell carcinoma - Jian-lin Huang; Yong Liao; Ming-xing Qiu; Jun Li; Yu An (Tumor Biology, 2017)
Clear cell renal cell carcinoma (ccRCC) is a common urologic malignancy. Long non-coding RNA colon cancer–associated transcript 2 (CCAT2) has been suggested as serving pivotal roles in tumorigenesis. However, the clinical significance and biological role of CCAT2 in ccRCC remains elusive. The purpose of this study is to identify the function of CCAT2 in ccRCC and its possible molecular mechanism. Expression of CCAT2 was analyzed in 61 ccRCC tissues and two ccRCC cell lines (786-O and ACHN) by quantitative reverse transcription polymerase chain reaction. The functional roles of CCAT2 in ccRCC were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, colony formation assay, Transwell assay, and flow cytometric analysis. The influence of CCAT2 on tumorigenesis was monitored by in vivo mice xenograft model. The activation of Wnt/β-catenin signaling pathway was evaluated by the TOP/FOP Wnt luciferase reporter assay and western blot assay. CCAT2 expression was markedly higher in ccRCC cell lines and tissues, being positively associated with tumor size and tumor stage in ccRCC patients. Patients with higher CCAT2 expression had a markedly poorer overall survival than did patients with low CCAT2 expression. Knocking down CCAT2 expression led to reduced cell proliferation and increased apoptosis of ccRCC cells in vitro as well as the activation of Wnt/β-catenin signaling pathway, and CCAT2 overexpression remarkably enhanced these oncogenic properties. In vivo mice xenograft model also showed that knocking CCAT2 expression inhibited the growth of ccRCC xenografts. In conclusion, these results indicated that CCAT2 may play a critical role in ccRCC progression and will be further considered as a biomarker for predicting the survival of ccRCC patients and a potential therapeutic target for ccRCC intervention.